Genesis, morphology and mineralogy of Planosols developed from different parent materials in southern Brazil - da Silva, Luís Fernando; Fruett, Tatiele; Zinn, Yuri Lopes; Inda, Alberto Vasconcellos; do Nascimento, Paulo César (Geoderma, 2019)
The genesis of Planosols is a complex process since it can involve multiple cycles of soil formation, deposition of allochthonous materials and also past climate changes. Furthermore, this subject is still poorly studied in the humid tropics, thus hindering a proper appraisal of the potentials and limitations of Planosols. The objective of this research was to study pedogenetic processes and properties of Planosols formed from different parent materials in southern Brazil. Four soils were sampled: (P1) Hypereutric Luvic Albic Planosol, developed on lagoon plain sediments; (P2) Orthoeutric Luvic Albic Planosol, on Holocene alluvial deposits; (P3) Hypereutric Luvic Albic Planosol, on granite; and (P4) Orthoeutric Luvic Albic Planosol, on gneiss. All Planosols presented sandy horizons A and E, with low pH (<5.0), CEC (<5cmolckg−1 soil) and base saturation (<50%), despite having high-activity clays. The Planosols presented high levels of amorphous aluminum hydroxides at the top of Bt horizons, suggesting Al mobilization by the pedogenetic process of ferrolysis. Micromorphological observation of clay coatings also confirmed the pedogenetic process of lessivage in all Planosols, in accord with strong texture gradients between E/Bt horizons. Quartz is practically the only primary mineral present in sand fractions and thin sections, suggesting a strong weathering. The X-ray diffraction showed small feldspar and quartz peaks in the clays, which were dominated by interstratified kaolinite-smectite, probably stabilized by strongly restricted drainage, and which imparted the high clay activity, unusual in nearby soils. Although the Planosols studied differed in parent material, the composition of the clays was strikingly similar, suggesting the predominance of ferrolysis, illuviation and associated processes in producing Albic Planosols. •Four Planosols developed from different parent materials were studied.•Thin sections showed advanced weathering and clay coatings in E/Bt transition.•An unusual kaolinite/smectite interstratified clay formed in all Planosols.•Strong weathering and restricted drainage favored the formation of such clay.•Multiple processes (ferrolysis and clay translocation) contributed to formation of the abrupt textural change in the soils.